2021
DOI: 10.1371/journal.pntd.0009154
|View full text |Cite
|
Sign up to set email alerts
|

Household rat infestation in urban slum populations: Development and validation of a predictive score for leptospirosis

Abstract: Domestic rats are the principal reservoir for urban leptospirosis. However, few studies have identified infestation markers in slums and evaluated their predictivity for leptospirosis risk. We compared households with leptospirosis cases in Salvador, Brazil between 2007 and 2009 and their neighbors using a case control design, surveying for rodent infestation signs and environmental characteristics. With the 2007–2008 data, a conditional logistic regression modeling identified the peridomiciliar presence of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
4
9
0
Order By: Relevance
“…The finding that rattiness was associated with infection risk indicates that the spatial distribution of rat populations was an important driver of transmission close to the household across the entire study area. This is consistent with a recent study investigating the predictive power of household rat infestation scores for human infection ( Costa et al, 2021 ). There was no residual spatial correlation in the infection data after accounting for rattiness in our analysis, possibly suggesting that previously unexplained spatial heterogeneity in risk could be driven by variation in rattiness ( Hagan et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding that rattiness was associated with infection risk indicates that the spatial distribution of rat populations was an important driver of transmission close to the household across the entire study area. This is consistent with a recent study investigating the predictive power of household rat infestation scores for human infection ( Costa et al, 2021 ). There was no residual spatial correlation in the infection data after accounting for rattiness in our analysis, possibly suggesting that previously unexplained spatial heterogeneity in risk could be driven by variation in rattiness ( Hagan et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that rat abundance may be predictive of environmental risk, and could be used as a proxy for this shedding process. While several studies have identified associations between infection risk and household rat sightings and infestation ( Reis et al, 2008 ; Costa et al, 2014b ; Hagan et al, 2016 ; Costa et al, 2021 ; Pellizzaro et al, 2019 ; Bhardwaj et al, 2008 ), their ability to explore fine-scale spatial variation in risk was limited by a reliance on household infestation surveys or aggregation of incidence and abundance indices to a common coarse spatial scale. All modelled abundance as a regression covariate, thereby not accounting for uncertainty in its measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that rattiness was associated with infection risk indicates that the spatial distribution of rat populations was an important driver of transmission close to the household across the entire study area. This is consistent with a recent study investigating the predictive power of household rat infestation scores for human infection [30]. There was no residual spatial correlation in the infection data after accounting for rattiness in our analysis, possibly suggesting that previously unexplained spatial heterogeneity in risk could be driven by variation in rattiness [12].…”
supporting
confidence: 91%
“…This suggests that rat abundance may be predictive of environmental risk, and could be used as a proxy for this shedding process. While several studies have identified associations between infection risk and household rat sightings and infestation [10,12,22,[29][30][31], their ability to explore fine-scale spatial variation in risk was limited by a reliance on household infestation surveys or aggregation of incidence and abundance indices to a common coarse spatial scale. All modelled abundance as a regression covariate, thereby not accounting for uncertainty in its measurement.…”
mentioning
confidence: 99%
“…Various authors have described the urban (con)formation of Salvador (and its segregation processes) from the point of view of housing (Brandão 1980, Mendonça 1989, de Carvalho 2002, Brito 2005, Fernandes, Regina 2005, Lima 2005, Soares, Espinheira 2006, Gordilho-Souza 2008, Santos 2012, Castro 2017, occupation and work (Carvalho, Pereira, 2018, Carvalho 2020, distribution of urban infrastructure (Silva 2015(Silva , 2019, mobility (Rocha 2014), provision of public spaces (Serpa 2006), environmental quality (Moraes et al 2003, Santos et al 2013) and health (Paim et al 1987, Souza 2005, Antunes et al 2013, Costa et al 2021.…”
Section: Objectives and Study Areamentioning
confidence: 99%